Pengaruh Perceived Quality of Product dan Perceived Quaility of Service terhadap loyalitas tamu di mediasi oleh kepuasan di The ZHM Premiere Hotel Padang - M Fachri; Youmil Abrian (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
The findings focus on the effects of perceived product quality (X1) and perceived service quality (X2) on guest loyalty (Y) and guest satisfaction (Z) as a mediating variable at The ZHM Premiere Hotel Padang. This study is classified as a quantitative descriptive study. The research approach used is causal-associative, while the data collection technique employed was a survey method. The sample consisted of 180 respondents who had stayed at least two nights or more. The results of the descriptive analysis indicate that (X1) perceived product quality falls into the “good” category (mean 4.04), (X2) perceived service quality is good (4.03), (M) guest satisfaction is good (4.15), and (Y) guest loyalty is good (4.13). In this study, data analysis was conducted using two methods: descriptive statistics and SEM-PLS. Meanwhile, hypothesis testing utilized t-statistics and p-values. Based on the findings, it was determined that: (1) Perceived product quality has a positive and significant impact on guest satisfaction. (t=4.070); (2) Perceived quality of service has a positive and significant impact on guest satisfaction (t=5.496) and Perceived quality of service has a large and significant impact on guest loyalty (t=2.606); (3) Guest satisfaction has a positive and significant influence on guest loyalty (t=5.567); (4) Perceived product quality does not have a direct effect on guest loyalty (t=0.866), but perceived product quality has a positive and significant effect on guest loyalty through the mediation of guest satisfaction (t=2.983); (5) Perceived service quality has a significant effect on guest loyalty both directly and through the mediation of guest satisfaction (t=4.028). All preliminary hypotheses proposed in this study were proven to be accepted except for the direct effect of X1 on Y.